The “New Majority” and the White Ethnics – The Involvement of László Pásztor in Richard Nixon’s Reelection Campaign in 1972 - Máté Gergely Balogh (Hungarian Cultural Studies)
The support of the “white ethnic” population was instrumental in Richard Nixon’s landslide presidential victory in 1972. Whereas traditionally, urban, working-class Catholics had been voting mostly for Democratic candidates, in 1972, the majority of them defected to the Republican Party. One of the most important ethnic organizers was the Hungarian 1956 émigré, László Pásztor. Pásztor was the director of the Heritage Groups (Nationalities) Division of the Republican National Congress, and his work among the volunteers strongly contributed to the result. But from the perspective of the Nixon campaign, Pásztor was not the ideal ethnic—he was critical of détente and was actively promoting ethnic interests such as ethnic hirings. Whereas the Nixon campaign wanted to focus on the urban, working-class ethnic demographic referred to as the “New Majority,” Pásztor was representing the anticommunist, captive nations narrative. Pásztor was predicting that this shift was going to hurt the Republican Party electorally, as the anticommunist ethnics would feel that their interests were ignored.